Implementation of Sharia Audit: Perception of Sharia Accounting Students - Novendi Arkham Mubtadi; Hendri Hermawan Adinugraha (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to explore how students’ perceptions of the application of sharia audits are seen from the issues of the sharia audit framework, the scope of sharia audits, sharia auditor qualifications, and the independence of sharia auditors. The research used survey study methods to obtain qualitative and quantitative data through a descriptive approach, and the data sources were primary data. The population and sample in this study were the 32 Sharia Accounting Students from the Faculty of Islamic Economic and Business, Islamic State Institute of Pekalongan, who took Auditing Concentration (Class of 2018), the data collection method used was a questionnaire. The results of the study concluded that: (1) sharia accounting students have a positive perception of sharia audits viewed from the aspect of the sharia audit framework; (2) students have a positive perception of relating to the perception of sharia audit seen from the aspect of the scope of sharia audits; (3) sharia accounting student have a positive perception of sharia audits viewed from the aspect of sharia auditor qualifications; (4) sharia accounting students have a very positive perception of sharia audits seen from the aspect of sharia auditor independence. Sharia accounting students have a positive perception of sharia auditing from the aspects of the sharia audit framework, the scope of sharia auditing, and the qualifications of sharia auditors, as well as very positive perceptions of the aspects of the independence of sharia auditors.